A democratização da gestão da política de assistência social em Londrina/PR no período 2001-2004: a ampliação do acesso e da participação - Pastor, Márcia (2006)
This study analyzes the Social Assistance Policy s democratization process in the city of Londrina-Pr, between 2001 and 2004. It examines the comprehension of managers, municipal council counselors, directors of social assistance institutions, social workers and users about the effectiveness of this policy based on the citizen s rights. Its theoretical framework includes the issues of management and democratization and also the actual key elements of the Social Assistance Policy. A qualitative research was done for the documental analysis and the semi-structured interviews. The data revealed the comprehension of the democratization as a means to make viable the access to social rights and to participation. The analysis about the democratization of the management was based on two axis: the effectiveness of the rights and the broadness of the participative process. The rise of the funds made possible the quantitative and qualitative amplification of the social assistance programs and the implementation of the Regional Centers of Social Assistance. The actions of the Municipal Council were highlighted by the exercise of the social control. The democratization was confirmed as a management qualifying component and was incorporated in the practice of the managers and professionals